Siaran Budaya Sebagai Upaya Melestarikan KebudayaanDaerah Melalui Program Acara di TVRI D.I.Yogyakarta - Dewi, Mutia (KOMUNITAS, 2014)
Television is one of the mass media which has the power to influence the public through broadcast programs. Television power be able to change the behavior and culture through entertainment or violence program. Therefore dominating entertainment programs and shows violence on television, this study wanted to see how the efforts to be made by TVRI D.I. Yogyakarta as public broadcasters to preserve localculture through the production of cultural programs by category, as well as supporting factorsand obstacles in an effort preserving local culture through broadcasting programs. The data obtained through interviews, documentation and observation. The results show the percentage ofprograms with cultural themes comprising approximately 14.21% of the pangkur jenggleng, obrolan angkringan, cangkriman, karangtumaritis, ketoprak, keroncong, and konser jawa.